Endocrine abnormalities in HIV‐infected women are associated with peak viral load – the Children and Women: AntiRetrovirals and Markers of Aging (CARMA) Cohort. (20th October 2015) - Sokalski, Kristen M.; Chu, Jackson; Mai, Alice Y.; Qiu, Annie Q.; Albert, Arianne Y.K.; Zanet, DeAnna L.; Côté, Hélène C.F.; Maan, Evelyn J.; Pick, Neora; Prior, Jerilynn C.; Money, Deborah M.; Murray, Melanie C. M.; et al.
Summary: Objectives: To investigate the prevalence of endocrine disturbances in a group of HIV‐positive (HIV+) women and to identify factors affecting presence of these disorders. To examine specifically whether cellular ageing, as measured by leukocyte telomere length (LTL), is correlated with the presence of endocrine disturbance. Design: A cross‐sectional retrospective substudy of an ongoing prospective cohort study. Patients: Adult HIV+ (≥19 years) women enrolled in the CARMA (Children and Women: AntiRetrovirals and Markers of Aging) cohort study ( N = 192). Prevalences of T2DM, glucose intolerance, dyslipidaemia, thyroid disorders, adrenal insufficiency, hypogonadism, primary ovarian insufficiency (POI), demographics, HIV and hepatitis C virus (HCV) infection status, baseline LTL, combined antiRetroviral therapy (cART) and substance exposures were collected. Statistical analysis included univariable followed by multivariable Poisson regression and step‐wise reduction to refine the multivariable model. Results: Prevalence of any endocrine abnormality was 58% (dyslipidaemia 43%, glucose intolerance/T2DM 13%, thyroid disorders 15%). In multivariable analysis, age was associated with number and type (any, glucose, lipid) of abnormality, while increasing body mass index (BMI) was associated with number of diagnoses and with glucose metabolism disorders. Interestingly, peak HIV pVL ≥100 000 copies/ml was associated with any abnormality, total number of disorders and presence of a thyroid disorder, while any disorder, glucose abnormalities and dyslipidaemia were negatively associated with alcohol use. LTL was not associated with number or type of endocrine abnormalities in this study. Conclusion: Further studies examining the relationship between duration and extent of exposure to HIV viraemia in relation to developing abnormal endocrine function are warranted.